2013
DOI: 10.5581/1516-8484.20130126
|View full text |Cite
|
Sign up to set email alerts
|

Blood discard rate and the prevalence of infectious and contagious diseases in blood donors from provincial towns of the state of Paraná, Brazil

Abstract: BackgroundSo that an improvement in the selection of donors can be achieved and the risk to the recipient of transfused blood can be reduced, prospective donors are submitted to clinical and serological screening. ObjectiveThis study investigated the blood discard rate and the rate of infectious and contagious diseases in blood donors from provincial towns of the state of Paraná, Brazil. MethodsThis study was an exploratory cross-sectional descriptive investigation with a quantitative approach of donations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
5
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
4
5
0
3
Order By: Relevance
“…Indeed, 57.1% of the discard rate was associated with HBV, followed by HIV (21.4%), HCV (7.1%), syphilis (10.7%) and malaria (3.6%) (Figure 1). A 57% rate of discard units due to HBV infection herein was consistent with other reports such as in Brazil with 52.5% of discarded blood units due to HBV seropositivity [26]; two additional studies indicated HBV reactivity that reached up to 54.8% [27] and 71.3% [28] of discarded blood units, confirming the high prevalence of this virus in Brazil [27].…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, 57.1% of the discard rate was associated with HBV, followed by HIV (21.4%), HCV (7.1%), syphilis (10.7%) and malaria (3.6%) (Figure 1). A 57% rate of discard units due to HBV infection herein was consistent with other reports such as in Brazil with 52.5% of discarded blood units due to HBV seropositivity [26]; two additional studies indicated HBV reactivity that reached up to 54.8% [27] and 71.3% [28] of discarded blood units, confirming the high prevalence of this virus in Brazil [27].…”
Section: Discussionsupporting
confidence: 79%
“…36 For this study, the prevalence of syphilis was 0.41% which reinforces similar findings in the study of Borelli et al. 37 at the Blood Center of Maringá, Paraná. On the other hand, the positivity rate for the pathology in Guarapuava (PR) was 2.1%, so a higher rate than that reported in the current study.…”
supporting
confidence: 91%
“…Research in other states of blood centers also showed a high positivity rate for syphilis testing, as well as in the Brazilian states of Amazonas, São Paulo and Sergipe. 37 Regarding the prevalence of syphilis, which in this study was 0.41% and hepatitis B (0.77%), together have demonstrated a high disability rate serologic, corroborating studies by Rodriguez et al, 38 Salles et al, 39 Carrazone et al, 22 and data obtained from the National Health Surveillance Agency. 40 The prevalence of hepatitis B and syphilis as the main pathologies associated with serological screening may be linked to the fact that currently the population has a cumulative effect of behavioral risks.…”
supporting
confidence: 91%
“…Compared with the prevalence of other diseases with mandatory notification at blood centers, our findings presented rates similar to those observed for hepatitis C virus (HCV) and hepatitis B virus (HBV) and higher than the rates observed for human immunodeficiency virus (HIV) and Chagas disease (10).…”
mentioning
confidence: 61%